Analisis Kadar Sakarin pada Beberapa Minuman Kemasan Bermerek yang Diperjualbelikan di Mall Uit Jalan Abdul Kadir Kota Makassar - Yunita Wandira; Sri Rahayu Ilyas; Nardin Nardin (Jurnal Media Laboran, 2018)
"An '' Analysis Of Sakarin Construction In Some Of The Beauty Packed Beverages In Mall Uit Kota Makassar '' Has Been Carried Out. The Purpose Of This Study Is To Find Out Whether There Is Saccharine In Branded Packaging Drinks That Are Traded At Uit Mall, Jalan Abdul Kadir, Makassar City And Find Out About Saccharine Levels In Branded Packaging Drinks That Are Traded At Uit Mall, Jalan Abdul Kadir, Makassar City. The Type Of Research Used Is Descriptive By Providing An Overview Of Sweeteners And Sweeteners In Traditional Cakes Traded In Hartako Market, Makassar City. The Sample In This Study Is As Many As 3 Types Of Packaging Drinks, Sampling Techniques Are Simple Random Sampling Or Random Techniques. This Research Was Conducted With Qualitative Tests And Quantitative Tests On 21-22 May 2019 At The D3 Laboratory Of Health Analysts At The University Of East Indonesia. The Results Of Laboratory Tests On Food Sweetening Substances On Traditional Cakes Qualitative Tests Showed Positive Results Containing Synthetic Sweeteners Namely Saccharin And Quantitative Tests Obtained Food Sweeteners Content Namely Saccharin In Samples A, B, And C Respectively 4.14%, 1.31% And 1.20%.